SOCIAL RESPONSIBILITY OF UNIVERSITIES - MacDonald, Kent (My University, 2013)
“In these times of increased access and declining resources we need to think more broadly about the responsibilities of our universities. Let me end as I started. We do not want to create a series of universities that have the same mission and purpose. Differentiation is not only good; it is necessary. However, in my mind, if I were to prioritize two responsibilities of the university of today, they would be to serve as economic catalyst and play the role of innovation generator.”--
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; university mission; university responsibility; higher education; education reforms